LA LUCHA ENTRE EL OLIMPO Y LA REPÚBLICA: CULTURAS POPULARES, VIOLENCIA POLÍTICA Y LA BÚSQUEDA DE ACUERDOS EN LA COSTA RICA DE CAMBIO DE SIGLO, 1889-1910 - Díaz Arias, David (2024)
This paper is part of the new historical analyses of Costa Rica’s democracy and politics that appeared during the 1990s in an attempt to rethink political culture in Costa Rica during the so-called Liberal Republic (1870-1930), by understanding electoral fraud as a fundamental part of this country’s democratic game and by revealing the different social and political connections and interests between popular cultures and political classes. In that sense, this work conceptualizes violence as part of the political struggle in which second and first-degree voters, local caudillos, party elites and the presidency of the republic converged. Moreover, this paper studies Costa Rican political groups’ search for political agreements as a tool to heal hatreds and disputes that took place during 1889-1897. This paper emphasizes the analysis of subaltern groups and local caudillos in an attempt to unveil their historical agency in the transformations that led to the political-electoral reforms in Costa Rica at the beginning of the 20th century.